AKTUALISASI DAKWAH DALAM PERSPEKTIF TRANSFORMASI SOSIAL - Khoiruddin Khoiruddin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2012)
All dakwah activities can be regarded as a process of social transformation in creating fundamentally a better society. Dakwah (Islamic preaching) is the command of Allah to mankind for carrying out a social transormation for the sake of the man himself. The strategy includes giving birth to transformative forces either in the weak people who do not get benefit from the structure, or the creators of the structure, while the agenda includes the need to establish a clear vision and pradigm of social change; that is, first, creating a room that provides an opportuunity to do self-actualization under the pressure of unjust structures and systems; second, the need to fundamentally revise the approaches and mthodologies of existing practices during this mission, including revisiting the themes of dakwah, methods of training and research in the preparation of human resources in dakwah activities.